Practical approach to the gastrointestinal manifestations of cystic fibrosis. (16th May 2018) - Bolia, Rishi; Ooi, Chee Y; Lewindon, Peter; Bishop, Jonathan; Ranganathan, Sarath; Harrison, Jo; Ford, Kristyn; van der Haak, Natalie; Oliver, Mark R
Abstract: Cystic fibrosis (CF) is the most common, life‐shortening, genetic illness affecting children in Australia and New Zealand. The genetic abnormality results in abnormal anion transport across the apical membrane of epithelial cells in a number of organs, including the lungs, gastrointestinal tract, liver and genito‐urinary tract. Thus, CF is a multi‐system disorder that requires a multi‐disciplinary approach. Respiratory disease is the predominant cause of both morbidity and mortality in patients with CF. However, there are significant and clinically relevant gastrointestinal, liver, pancreatic and nutritional manifestations that must be detected and managed in a timely and structured manner. The aim of this review is to provide evidence‐based information and clinical algorithms to guide the nutritional and gastrointestinal management of patients with CF.